Towards a sustainable alcohol control framework: policy gaps and opportunities in Mojokerto Regency - Muhammad Roisul Basyar; Joko Widodo; M. Noer Falaq Al Amin (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
Mojokerto Regency is known as one of the largest producers of alcoholic beverages in Indonesia, with production from PT Multi Bintang and home-made alcoholic beverages. This study analyzes the implementation of alcoholic beverage control and supervision policies in Mojokerto Regency using the Van Meter and Van Horn models. The research method uses a qualitative approach with data collection through in-depth interviews with key stakeholders from the Industry and Trade Service and the Civil Service Police Unit. The results of the study show three main findings: (1) There is a lack of clarity in the standards and objectives of the policy as reflected in the absence of official permit applications since the enactment of the 2016 Regional Regulation; (2) Although the structure of the Integrated Team across agencies has been designed, its implementation is hampered by the absence of an official Decree legitimizing the team's authority; (3) There is a significant gap between regulation and implementation as indicated by the failure of the monitoring and evaluation system. The main challenges lie in the weak coordination between agencies, limited data on the circulation of alcoholic beverages, and resistance from business actors. This study recommends the need to strengthen institutional aspects through the formalization of the Integrated Team, development of an integrated data collection system, and increased coordination between related agencies.